Government bonds yield (SBN-Domestic), IDX Composite (IHSG), US-Treasury Bonds yield 10 years, and SP500 linkages: a VAR model approach - Martono Tampubolon; Buddi Wibowo (President University, 2022)
The US is the country with the largest economy in the world. With the largest GDP among the G20 countries, the US power in influencing the world economy is also large. All economic, social, and political shocks that occur in the United States will be transmitted to emerging market countries such as Indonesia. This transmission will affect the performance of government bonds and the Indonesian stock market. This paper describes the type of relationship (response) that occurs between the yield of SBN Domestic variables (SBN20Y, SBN15Y, SBN10Y, SBN5Y, and SBN3Y), market index return volatility (IHSG) to the sources of shocks, and transmitting from yield variables T-Bond10Y, and SP500. The empirical model used to measure the type of relationship that occurs is by implementing a VAR (Vector Autoregression) model. The findings prove that there are dynamic linkages between the variables yield of SBN20Y, yieldSBN15Y, and yield SBN10Y on shocks originating from the yield of T-Bond10Y. The yield of SBN3Y has dynamic linkages to shock originating from the volatility of the SP500, and others have a contemporaneous relationship. The results of this study are expected to be able to add to the literature in the field of finance and investment, provide input for investors in investment decisions in determining which assets will be included in their portfolio, and last the findings of this paper in hoping contributes to the policy makers (government) in how they keep the domestic economic stability.